2014
DOI: 10.1088/1674-1056/23/3/038505
|View full text |Cite
|
Sign up to set email alerts
|

High performance pentacene organic field-effect transistors consisting of biocompatible PMMA/silk fibroin bilayer dielectric

Abstract: Pentacene organic field-effect transistors (OFETs) based on single-or double-layer biocompatible dielectrics of poly(methyl methacrylate) (PMMA) and/or silk fibroin (SF) are fabricated. Compared with those devices based on single PMMA or SF dielectric or SF/PMMA bilayer dielectric, the OFETs with biocompatible PMMA/SF bilayer dielectric exhibit optimal performance with a high field-effect mobility of 0.21 cm 2 /Vs and a current on/off ratio of 1.5×10 4 . By investigating the surface morphology of the pentacene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Silk films are non-immunogenic, mechanically flexible, show great surface quality and have optical transparency and controllable degradation rate (188)(189)(190). Furthermore, silk fibroin was shown to exhibit excellent electrical insulating properties, for which reason it is often chosen as the gate dielectric in organic thin-film transistors (191)(192)(193)(194)(195). Depending on application, silk films can be patterned with controllable thickness and porosity, and chemically modified with growth or adhesion factors.…”
Section: Silkmentioning
confidence: 99%
“…Silk films are non-immunogenic, mechanically flexible, show great surface quality and have optical transparency and controllable degradation rate (188)(189)(190). Furthermore, silk fibroin was shown to exhibit excellent electrical insulating properties, for which reason it is often chosen as the gate dielectric in organic thin-film transistors (191)(192)(193)(194)(195). Depending on application, silk films can be patterned with controllable thickness and porosity, and chemically modified with growth or adhesion factors.…”
Section: Silkmentioning
confidence: 99%
“…Other studies have also demonstrated the successful application of silk as a substrate in implantable electronics [28,68] and food sensors [69]. Applications of silk in dielectrics were also reported [29,70,71,72,73,74,75,76,77]. Liang et al [70] fabricated organic thin-film transistors (OTFTs) with silk as their dielectric layer.…”
Section: Biodegradable and Biocompatible Polymersmentioning
confidence: 99%
“…Meanwhile, the results showed that the memory window was proportional to the amount of traps in PVA and the charge density at the interfaces of gate/PVA or PVA/pentacene. Then, the pentacene OFETs based on bilayer dielectrics of PMMA/SF was developed, as shown in Figure 1(b) [23]. The PMMA/SF bilayer dielectric exhibited a high field-effect mobility of 0.21 cm 2 /Vs and a high current on/off ratio of 1.5 × 10 4 .…”
Section: Multilayer Polymer Dielectricmentioning
confidence: 99%
“…Yu et al reported an enhanced performance pentacene OFETs consisting of PMMA/SF bilayer dielectric in 2014 [23]. The SF had good dielectric properties as shown in Figure 4(b).…”
Section: Silk Fibroin Dielectricmentioning
confidence: 99%